Interprofessional work in health in the context of the COVID-19 pandemic: a scoping review - Fernandes, Sâmara Fontes; Trigueiro, Jaira Gonçalves; Barreto, Márcio Adriano Fernandes; Carvalho, Rhanna Emanuela Fontenele Lima de; Silva, Maria Rocineide Ferreira da; Moreira, Thereza Maria Magalhães; Costa, Marcelo Viana da; Freitas, Rodrigo Jácob Moreira de (Revista da Escola de Enfermagem da USP, 2021)
Objective: to map the scientific production on interprofessional relationships in health in the first year of the COVID-19 pandemic. Method: this is a scoping review performed in PubMed, Scopus, LILACS, CINAHL, Web of Science, Google Scholar and Science Direct databases, covering the period of publication in 2020, using the acronym PCC (Population = health professionals; Concept = interprofessional relationships; Context = health services) and respective search strategies. Results: fourteen scientific articles were selected and the content discussed in the manuscripts was standardized, analyzed and organized into categories of affinities and similarities of their results: 1 – Interprofessional collaboration; 2 – Collaborative practice; 3 – Interprofessional work; 4 – Interactive and interprofessional learning. Conclusion: the pandemic demanded quick and effective responses that were only possible through collaboration and interprofessionalism dimensions. Interprofessional work in health during the first year of the COVID-19 pandemic confirms the importance of interprofessional work and its dimensions for the provision of more comprehensive, resolute and safer health services.